License Plate Identification from Myanmar Vehicle Images under Different Environmental Conditions - Ohnmar Khin; Montri Phothisonothai; Somsak Choomchuay (My University, 2018)
car license plate recognition (CLPR)
Keywords: Identification; Vehicle License Plate Recognition